Holst, The planets - Greene, Richard (Cambridge music handbooks, 1995)
This book is the first comprehensive guide to Holst's popular orchestral suite The Planets. It considers the music in detail and places the work in its historical context, describing the circumstances of its composition and its meteoric rise to popular acclaim. Starting with Holst's particular interest in astrology, Professor Greene explores the plotting of the work's central melodic and harmonic gestures to reveal a profound statement of human character and Holst's own psychological journey toward the mystic state. Using parallels in the verbal arts Greene weaves a fascinating tale of musical communication. An understanding of The Planets is crucial to a full appreciation of Holst's profound late works, and Greene's systematic appraisal provides the first revealing light in this direction